Light-cone gauge in non-relativistic AdS5 ×S5 string theory - Andrea Fontanella; Juan Miguel Nieto García (Journal of High Energy Physics, 2023)
Abstract We discuss the non-relativistic limit of string theory in AdS5×S5 for different choices of embedding coordinates. We show that, if we consider Cartesian coordinates, the action of fluctuations around the twisted BMN-like string found in arXiv:2109.13240 in uniform light-cone gauge becomes the one of free fields at large string tension and large AdS5 radius.